The Balanced Scorecard Approach in Performance Measurement of The Pharmacy Installation of X Hospital Pangkalpinang - Ratih Puspita Kusumadewi Purba; Syamsul Rizal Sinulingga (Poltekkes Kemenkes Pangkalpinang, 2019)
Balanced Scorecard was developed as a performance management system that sees the company's overall performance through four perspectives: financial; the customer; internal business processes; learning and growth. Cooperation with the Government to serve the patients of the national health coverage needs to be accompanied by good performance especially of human capital, informational capital, and the organizational capital in order to improve the quality of service. This research aims to determine the performance of Pharmacy Installation of X Hospital Pangkalpinang on learning and growth perspective with the Balanced Scorecard approach. This research is a descriptive research. The subjects of the research are head of pharmacy, employee pharmacy, personnel data, employee training data in accordance with the indicators contained in the learning and growth perspective. The results show that there is 100% of employee retention, employee training showed improvement, and management information systems capabilities have been available. Indicators that need to be improved is adequacy of pharmacists, the satisfaction of employees, organizational culture, organizational climate, leadership, team work, and alignment.